Investigation on Image Denoising Techniques of Magnetic Resonance Images - Kalaiselvi, T; Kalaichelvi, N (International Journal of Computer Sciences and Engineering, 2025)
MR images are mostly used for clinical diagnosis for their accuracy. Even though the resolution, signal-to-noise ratio and acquisition speed have been increased, the MR images are still getting polluted. Thus, denoising is needed to be done in order to improve the accuracy of both the manual and computer aided diagnostic process. There are number of noises in digital images caused based on the nature of image acquisition or transformation. Rician noise is the kind of noise occurs in MR images. Numerous denoising techniques have been proposed to denoise Rician distribution in MR images. In this paper a survey about noises in digital images, non-local means (NLM) filtering and wavelet based MRI denoising techniques have been done. Finally, a Rician denoising method is proposed using wavelet thresholding and Rician NLM and compared with the existing methods. The PSNR values show that the proposed method yields better results.